Bad Rabbit ransomware attacks Russia and Ukraine. Issue 11 (November 2017) - Unknown
Abstract : There has been another outbreak of ransomware, with some similarities to the NotPetya attacks – although there are also significant differences. So far, the malware seems to have mostly affected targets in Russia and Ukraine, with a handful of victims in Turkey and Germany, although it's possible it could spread further.